2019
DOI: 10.1093/ajcn/nqz041
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation improves glycemic control for diabetes prevention and management: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Although many studies have shown that low zinc status is associated with diabetes, the putative effects of zinc supplementation on glycemic control are inconclusive. Objectives The aim of this meta-analysis of randomized controlled trials was to assess the effects of zinc supplementation in preventing and managing diabetes. Methods PubMed, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 65 publications
6
62
0
9
Order By: Relevance
“…The study showed significant lower levels of glucose as well as correspondingly lower risk of elevated glucose level in USANA CS users (Tables 2 and 3, Figure 3). This is consistent with previous studies that showing folate [79], vitamin E [80], -C [81], -B6 [82], -B12 [83], niacin [84], thiamine [85], magnesium [58], chromium [60], zinc [86] and copper [87,88] have some beneficial effects on insulin action, glycaemic control and endothelial function. Notably, a meta-analysis of 18 trials with 21,081 subjects reported that folate supplementation significantly decreased glucose level [79].…”
Section: Discussionsupporting
confidence: 93%
“…The study showed significant lower levels of glucose as well as correspondingly lower risk of elevated glucose level in USANA CS users (Tables 2 and 3, Figure 3). This is consistent with previous studies that showing folate [79], vitamin E [80], -C [81], -B6 [82], -B12 [83], niacin [84], thiamine [85], magnesium [58], chromium [60], zinc [86] and copper [87,88] have some beneficial effects on insulin action, glycaemic control and endothelial function. Notably, a meta-analysis of 18 trials with 21,081 subjects reported that folate supplementation significantly decreased glucose level [79].…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the hypothesized protective role of Zn has not been well demonstrated in human studies. Dietary intake [12] or supplementation [21] of Zn seemed to regress the progression of new-onset DM, whereas serum Zn had no association with DM in meta-analyses [9][10][11]. Besides, total zinc intake from both diet and supplementation failed to demonstrate the protective role toward diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…The use of omega-3 s for prevention of cardiovascular events has been controversial however the most recent meta-analysis of 127,477 participants demonstrates lower risk of cardiovascular events including AMI, CHD death, and total CVD death [157] with marine omega-3 supplementation. Coenzyme Q10 may be beneficial in heart failure [158] T2D: Zinc [159], curcumin [160], Coenzyme Q10 [161], probiotics [162,163], and chromium [164] have been demonstrated to have beneficial effects on glycemic control and cardiovascular risk factors in meta-analyses in people with T2D…”
Section: Integrative Medicinementioning
confidence: 99%